Acts of Assembly Relating to Fairmount Park 18 (1868) - (:unkn) unknown (My University, 1868)
§ 21: No persons shall carry fire-arms, or shoot birds in the Park, or within fifty yards thereof, or throw stones or other missiles therein.
Keywords: CARRY; DISCHARGE